Tracking sectoral progress in the deep decarbonisation of energy systems in Europe. (November 2017) - Spencer, Thomas; Pierfederici, Roberta; Sartor, Oliver; Berghmans, Nicolas; Samadi, Sascha; Fischedick, Manfred; Knoop, Katharina; Pye, Steve; Criqui, Patrick; Mathy, Sandrine; Capros, Pantelis; Fragkos, Panagiotis; et al.
Abstract: Decarbonisation of energy systems requires deep structural change. The purpose of this research was to analyse the rates of change taking place in the energy systems of the European Union (EU), in the light of the EU's climate change mitigation objectives. Trends on indicators such as energy intensity and carbon intensity of energy were compared with decadal benchmarks derived from deep decarbonisation scenarios for the electricity, residential, transport, and industry sectors. The methodology applied provides a useful and informative approach to tracking decarbonisation of energy systems. The results show that the EU has made significant progress in decarbonising its energy systems. On a number of indicators assessed the results show that a significant acceleration from historical levels is required in order to reach the rates of change seen on the future benchmarks for deep decarbonisation. The methodology applied provides an example of how the research community and international organisations could complement the transparency mechanism developed by the Paris Agreement on climate change, to improve understanding of progress toward low-carbon energy systems. Highlights: A methodology to track the decarbonisation of EU energy systems is proposed. Decarbonisation rates in electricity, residential, transport and industry sectors are analysed. EU Member States have made significant progress in decarbonising their energy systems. An acceleration in the rates of decarbonisation in some sectors appears necessary.